Efektivitas Biopestisida Metarhizium Sp. Dalam Mengendalikan Belalang Kembara (Locusta migratoria minilensis Mayen) - Maranda, Adelita Putri; Killa, Yonce Melyanus; Kapoe, Suryani K.K.L (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
Locust pests are one of the most critical pests in almost every region of Indonesia. This pest phenomenon occurs because biological and environmental factors influence it. The significant use of chemical pesticides can cause environmental damage. One of the alternatives in controlling locust pests is using biopesticides Metharizium sp. This study aimed to determine the effectiveness of Metarhizium sp. biopesticides against locusts. The method used in the study was a complete randomized design (CRD), with four treatments, repeated four times to obtain 16 experimental units M0: Without biopesticide Metarhizium sp.; M1: biopesticide Metarhizium sp. 20 ml + 80 ml distilled water; M2: biopesticide Metarhizium sp. 40 ml + 60 ml distilled water; M3: biopesticide Metarhizium sp. 60 ml + 40 ml distilled water. The study results showed that Metarhizium biopesticide significantly affected mortality and feeding activity at a dose of 60 ml Metarhizium biopesticide liquid + 40 ml distilled water (M3). The observations on day three show that Metarhizium biopesticide can kill the locust pests by slowly beginning to paralyze the power of movement and the power of eating activity, causing the locust pests to experience death. Symptoms on the body of dead pests range from blackish, black hardened, and white spots. This shows that Metarhizium fungus with a dose of 60 ml is the most effective treatment in controlling locust pests.